Higher Education is a Human Right - Heidi R. Gilchrist (Washington University Global Studies Law Review, 2018)
Higher education is a human right. In the United States, we have become complacent about the skyrocketing costs of higher education where yearly expenses at many highly selective universities well exceed the median income of United States workers. We need to change the dialogue about higher education so that it does not become a luxury only the wealthy can afford. This article examines the right to higher education under international law and argues that it is already an established right and not a luxury item. Additionally, not only is a higher education a human right, but it has an important national security value. Using the Syrian refugee crisis as an example, the world cannot risk a ‘lost generation’ of students who do not get the education they need to rebuild and lead their country and counter terrorist messages that breed in failed states. We need diversity in education and people with capacity from all backgrounds should be able to exercise their human right to education, at all levels.
Keywords: education; human rights; higher education